Implementation of Aqiqah in the Bulan Maulid in Nagari Padang Laweh West Sumatra Perspective'Urf - Sulfinadia, Hamda; Roszi, Jurna Petri; Rosdialena, Rosdialena; Suryani, Eli; Fitri, Anisa (Institut Agama Islam Negeri Curup, 2023)
This study aims to find out about the implementation of the aqiqah in the Maulid Nabi in Nagari Padang Laweh in terms of tradition. Aqiqah is an expression of gratitude for the birth of a child, which is basically the seventh or fourteenth day of birth or the twenty-first day. However, this did not happen to the Nagari Padang Laweh, the implementation of the aqiqah was held to coincide with the celebration of the Prophet's Birthday in the month Rabiul Awwal determined by custom. This ritual has been carried out from generation to generation and is still ongoing today. The implementation of the aqiqah will be reviewed from the ‘urf prevailing in the Islamic tradition. The research method used is qualitative with a case study approach. The primary data of this study were obtained through interviews with thirteen informants. After the data is collected, it is classified based on existing themes, then coded and analyzed with valid theory, and ‘urf so that conclusions can be drawn. The case study in this research relates to the implementation of the aqiqah along with the celebration of the Bulan Maulid. The results of the study show that the implementation of the aqiqah which coincides with the Bulan Maulid will provide relief to parents who participate in giving away their children. This is in line with Islamic law, and has proven to contain a lot problem. The conclusion from this research is that the implementation of the aqiqah includes urf shahih and local wisdom that needs to be preserved.